WSCUC Substantive Change Screening Form: B. A. in Theatre and Performance Studies
The Theatre and Performance Studies program at California State University Channel Islands provides an inclusive learning environment that promotes and values creativity, collaboration, community, and culture through embodied performance, on stage, on screen, and in everyday life. The degree offers students a strong foundation of performance skills in the areas of theatre as well as new media. Coursework is anchored in imagination, individual experiences, local and global awareness, current and historical events, and the performance traditions of diverse cultures, all as sources of artistic expression, intellectual inquiry, and human connection. Theatre and Performance Studies majors learn to use their voices both physically and metaphorically, to develop proficiency in storytelling and shared live presence, both in-person and virtual, and to cultivate and apply an understanding of how representation works and matters in performances on various twenty-first century stages and screens, and beyond.